IMPROVING STUDENT LEARNING ACTIVITIES THROUGH THE DEMONSTRATION METHOD - Rizatrisna Rizatrisna (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
This research is conducted due to the low of students activities. The purpose of this research is to increase student activity in learning. One of the actions taken by the researcher is through the demonstration method. This research was a classroom action research conducted on grade I students of SDN 42 Mandau with a total of 23 students. Data were collected using an observation sheet to observe teacher actions and student activities. The results showed that the demonstration method can increase the learning activities of 42 Mandau elementary school students with a percentage of teacher action by 56% and 59% of student activities included in the enough category in the first cycle. Then, the second cycle showed that an increasing with the percentage of teacher action by 79% and 80% of student activities with good category. Based on the results of the research, it can be concluded that the demonstration method can increase PAI learning activities for students in grade 1 at SDN 42 Mandau.